2011
DOI: 10.1080/01635581.2011.573900
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Apoptosis in Human Promyelocytic Leukemia HL60 Cells by an Extract FromErythrina suberosaStem Bark

Abstract: In this study, the apoptosis-inducing effect of an alcoholic extract from Erythrina suberosa stem bark (ESB) was investigated using human promyelocytic leukemia HL60 cells. Cell viability was estimated by MTT assay. We found that the ESB inhibited cell proliferation in a dose- and time-dependent manner. A series of well-documented morphological changes, such as cell shrinkage, condensation of nuclear chromatin, and nuclear fragmentation, were observed by fluorescence microscopy. The gold standard scanning elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Erythrina plant species are widely used in folk medicine to treat health conditions including agitation, insomnia, anxiety and inflammation (21,22). A previous study has revealed that an alcoholic extract of the stem bark of E. suberosa induces apoptosis in human promyelocytic leukemia HL-60 cells (23). The aim of the current study was to investigate the anticancer potential of the flavonoid wighteone isolated from the stem bark of E. suberosa, and to study HSP90 expression and its correlation with wighteone metabolite response in HER2-positive breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Erythrina plant species are widely used in folk medicine to treat health conditions including agitation, insomnia, anxiety and inflammation (21,22). A previous study has revealed that an alcoholic extract of the stem bark of E. suberosa induces apoptosis in human promyelocytic leukemia HL-60 cells (23). The aim of the current study was to investigate the anticancer potential of the flavonoid wighteone isolated from the stem bark of E. suberosa, and to study HSP90 expression and its correlation with wighteone metabolite response in HER2-positive breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Through human promyelocytic leukemia HL 60 cells, it has been found that stem bark of E. suberosa has apoptosis-inducing effects. [ 21 ] From aqueous leaf extracts of E. suberosa , biosynthesized silver nanoparticles were obtained, which were found with potentially effective anticancer activities. [ 18 ] Most of these studies were focused on leaf and flower extract, whereas our study was focused on the bark, and hence the results were nonetheless compatible with previous studies.…”
Section: R Esults and Discussionmentioning
confidence: 99%
“…Additionally, human cancer cell lines were investigated: HL60 (human promyelocytic leukemia) cells were tested with E. suberosa bark ethanolic extract [28]. Cell proliferation was inhibited in a dose-and time-dependent manner and the cell cycle was modulated by an increase in subG0/G1 cell phase.…”
Section: Pharmacological Propertiesmentioning
confidence: 99%